Utilizing yielding steel dampers to mitigate transverse seismic irregularity of a multispan continuous bridge with unequal height piers. (15th February 2020) - Xiang, Nailiang; Li, Jianzhong
Highlights: The effect of concrete shear keys on bridge seismic irregularity is investigated. Design principles for mitigating bridge seismic irregularity are determined. A simple yet practical design method is proposed for irregularity mitigation using yielding steel dampers. The well-designed steel dampers help achieve a uniform and balanced bridge seismic performance. Abstract: Multispan continuous bridges built in mountainous areas are typically characteristic of having equal height piers since it is a commonly-adopted solution when crossing steep-sided valleys. To prevent bridge unseating during strong earthquakes, exterior concrete shear keys are usually implemented in the transverse direction as displacement restraining devices. Due to the restraining effect of shear keys, unequal height bridges are very likely to display irregular seismic responses mainly by inducing significant in-plane superstructure rotations. A large superstructure rotation may impose unbalanced seismic demands at different substructures. In this study, yielding steel dampers were proposed to replace exterior shear keys to mitigate the irregular seismic responses of unequal height bridges. A practical design method was developed for the steel dampers to maintain a uniform superstructure movement and balance the seismic demands on different substructures. Deterministic (nonlinear time-history) and probabilistic (seismic fragility) dynamic analyses were conducted, which successfully verified the effectiveness of the proposed design method in achieving a regular and balanced seismic performance for the unequal height bridge.